The Impact of Separation Anxiety Disorientation on Children's Social Interaction - Ramadani, Sufi; Z, Sri Rahayu Putri; Yves, Caers; Tung, Ming Chiao (Yayasan Minang Darussalam, 2022)
Anxiety is a form of the body's response to the environment as a form of pressure and one's inner turmoil. This anxiety can be overcome easily, but in some cases anxiety often occurs excessively, especially in babies who are about to start a long phase of separation from their parents. This journal aims to find out how the social interaction of children with symptoms of separation anxiety disorder. The method in this research is a literature study, namely analyzing journals, books and articles that discuss separation anxiety disorder in children. This neglected anxiety disorder can have an impact on how the child begins to interact in a new environment later. It takes understanding and sensitivity of parents to the child's condition.